Rehabilitation exercise program after surgical treatment of quadriceps tendon rupture: A case report. (September 2019) - Vasiliadis, Angelo V.; Maris, Alexandros; Tsoupli, Aikaterini; Saridis, Antonios
Abstract: Objectives: This case report describes in detail the rehabilitation exercise program, provide post-operative therapeutic objectives/recommendations and to facilitate the return to a possible schedule of ADL and participation in sports after the surgical treatment of quadriceps tendon rupture. Also, the exact surgical technique is described. Design: A single case report. Participant: The patient was an active 53-year-old man who sustained this injury as a result of a sudden misstep with his left foot into a hole, while he was trekking across muddy countryside. Clinical examination of the knee revealed skin ecchymosis, swelling and tenderness over the distal thigh. Plain radiographs showed patella baja, and the scheduled magnetic resonance imaging (MRI) showed interrupted continuity of the quadriceps tendon and the patella. A diagnosis of quadriceps tendon rupture was made and the patient was scheduled to undergo surgical intervention the following day. Rehabilitation exercise program: A well-structured rehabilitation exercise program was followed in order to ensure rapid recovery and good functional outcomes. His postoperative course progressed normally, demonstrating a return to the normal activities of daily living at 6 weeks, full active range of motion at 16 weeks, and return to sports recreational activities at 5 months. Conclusions: An early surgical treatment and subsequently a well-structured rehabilitation exercise program have contributed to maximize the functional outcomes of the patient and provide a rapid and safe return to the activities of daily living (7th week) with participation in non-contact sports after the 18th week.